2010
DOI: 10.1088/0004-637x/719/1/307
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Spontaneous Formation of Stable Magnetic Structures on the Sun

Abstract: One of the puzzling features of solar magnetism is formation of long-living compact magnetic structures, such as sunspots and pores, in the highly turbulent upper layer of the solar convective zone. We use realistic radiative three-dimensional MHD simulations to investigate the interaction between magnetic field and turbulent convection. In the simulations, a weak vertical uniform magnetic field is imposed in a region of fully developed granular convection, and the total magnetic flux through the top and botto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
102
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(109 citation statements)
references
References 29 publications
7
102
0
Order By: Relevance
“…This makes NEMPI a viable mechanism for spontaneously producing magnetic spots in the surface layers. Our present study therefore supports ideas about a shallow origin for active regions and sunspots (Brandenburg 2005;Brandenburg et al 2010;Kitiashvili et al 2010;Stein & Nordlund 2012), contrary to common thinking that sunspots form near the bottom of the convective zone (Parker 1975;Spiegel & Weiss 1980;D'Silva & Choudhuri 1993). More specifically, the studies of Losada et al (2013) point toward the possibility that magnetic flux concentrations form in the top 6 Mm, i.e., in the upper part of the supergranulation layer.…”
Section: Discussionsupporting
confidence: 65%
“…This makes NEMPI a viable mechanism for spontaneously producing magnetic spots in the surface layers. Our present study therefore supports ideas about a shallow origin for active regions and sunspots (Brandenburg 2005;Brandenburg et al 2010;Kitiashvili et al 2010;Stein & Nordlund 2012), contrary to common thinking that sunspots form near the bottom of the convective zone (Parker 1975;Spiegel & Weiss 1980;D'Silva & Choudhuri 1993). More specifically, the studies of Losada et al (2013) point toward the possibility that magnetic flux concentrations form in the top 6 Mm, i.e., in the upper part of the supergranulation layer.…”
Section: Discussionsupporting
confidence: 65%
“…Such swirling motions correspond to vertically oriented vortex tube structures that have been found in numerical simulations [5,7,13]. The numerical simulations have demonstrated important links between vortex tube dynamics and processes of magnetic selforganization [2] and also with acoustic wave excitation [7] and have shown that vortex tubes play a fundamental role in solar magnetic flux dynamics. Also, small-scale horizontal vortex tubes located along granule edges were found both in numerical simulations and in observations with the balloon observatory SUNRISE [6].…”
Section: Introductionsupporting
confidence: 58%
“…They also state that "usually the process starts at one of the strongest vortices". We note that in the simulations of Kitiashvili et al (2010) the aspect ratio of the box is close to unity. Compared to our runs with aspect ratio four, we find that only a few large-scale convection cells are present in the deep layers; see Fig.…”
Section: Effective Magnetic Pressurementioning
confidence: 72%
“…8. This suggests that most likely only a single large-scale convection cell exists in the simulations of Kitiashvili et al (2010). This is not obvious from the flows at the surface where several vortical downflows, which are all connected to the same large-scale downflow at deep layers, can be identified.…”
Section: Effective Magnetic Pressurementioning
confidence: 95%